Antioxidant, Antimicrobial, and Anticancer Effects of Anacardium Plants: An Ethnopharmacological Perspective - Salehi, Bahare; Gültekin-Özgüven, Mine; Kirkin, Celale; Özçelik, Beraat; Morais-Braga, Maria Flaviana Bezerra; Carneiro, Joara Nalyda Pereira; Bezerra, Camila Fonseca; Silva, Teresinha Gonçalves da; Coutinho, Henrique Douglas Melo; Amina, Benabdallah; Armstrong, Lorene; Selamoglu, Zeliha; et al. (Frontiers in Endocrinology, 2020)
Anacardium plants are widely recognized for its nutritional and biotechnological attributes, but their bioactive effects have received a raising attention. Various beneficial secondary metabolites are present in its leaves, fruits and other plant parts, and multiple evidences have supported their uses for nutraceutical or therapeutic purposes. Among the various Anacardium plants’ bioactive effects, their antioxidant, antimicrobial and anticancer activities comprise those that have gained a higher visibility. Thus, the present review aims to provide an overview on Anacardium plants bioactive effects, specifically addressing their antioxidant, antimicrobial and anticancer effects. A special emphasis is also given to their pharmacological and clinical efficacy, towards to trigger more in-depth studies to investigate their therapeutic properties using well-designed clinical trials.